Coverage and equity of essential care services among stroke survivors in the Western Province of Sri Lanka: a community-based cross-sectional study - Nalinda Tharanga Wellappuli; Hettiarachchige Subashini Rasanja Perera; Thashi Chang; Gunendrika Kasthuriratne; Nalika Sepali Gunawardena (BMC, 2022)
Abstract Background Stroke survivors require continuing services to limit disability. This study assessed the coverage and equity of essential care services received during the first six months of post-stroke follow-up of stroke survivors in the Western Province of Sri Lanka. Methods A multidisciplinary team defined the essential post-stoke follow-up care services and agreed on a system to categorize the coverage of services as adequate or inadequate among those who were identified as needing the said service. We recruited 502 survivors of first ever stroke of any type, from 11 specialist hospitals upon discharge. Six months following discharge, trained interviewers visited their homes and assessed the coverage of essential services using a structured questionnaire. Results Forty-nine essential post-stroke follow-up care services were identified and categorized into six domains: monitoring of risk conditions, treatment, services to limit disabilities, services to prevent complications, lifestyle modification and supportive services. Of the recruited 502 stroke survivors, 363 (72.3%) were traced at the end of 6 months. Coverage of antiplatelet therapy was the highest (97.2% (n = 289, 95% CI 95.3- 99.1)) while referral to mental health services (3.3%, n = 12, 95% CI 1.4-5.1) and training on employment for the previously employed (2.2%, n = 4, 95% CI- 0.08-4.32), were the lowest among the six domains of care. In the sample, 59.8% (95% CI 54.76-64.48) had received an 'adequate' level of essential care services related to treatment while none received an 'adequate' level of services in the category of support services. Disaggregated service coverage by presence and type of limb paralysis within the domain of services to prevent complications, and by sex and education level within the domain of education level, show statistically significant differences (p < 0.05). Conclusions Apart from treatment services to limit disabilities, coverage of essential care services during the post-stroke period was inadequate. There were no apparent inequities in the coverage of vast majority of services. However focused policy decisions are required to address these gaps in services.